Social Skills - Singleton, W.T. author. aut Link
XIX, 307 p. 16 illus.
Keywords: W. T. SINGLETON THE CONCEPT This is the fourth in a series of books devoted to the study of real skills. A skilled person is one who achieves his objectives effectively, that is by an optimal expenditure of effort, attention and other resources working within his native capacities of strength, vision, intelligence, sensitivity and so forth. It is difficult if not impossible to measure in a quantitative sense. There is, however, no question about its presence or absence. The differences between a highly skilled performer and a mediocre one are so readily manifest that there is no ambiguity. The student of skill is a person interested in what these differences are and how they originate. The importance and the difficulty of skill study is that the concept is a univ~rsal one for human activity. The movement of one limb can be skilled or unskilled within the context of a task, so also can the way a leader addresses a large meeting of his followers. For these and other equally disparate activities there are certain descriptive terms which always seem to be applicable: continuity, sequencing, timing, together with a subtle combination of sensi tivity, adaptability and imperturbability. What happens at any instant is set precisely with the flow from what has already happened to what is going to happen. The order of events has a determinate logic which may not be obvious to the observer except with the benefit of hindsight.